2020
DOI: 10.2106/jbjs.oa.20.00051
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction and Functional Outcomes in Unicompartmental Compared with Total Knee Arthroplasty

Abstract: Background: Unicompartmental and total knee arthroplasty (UKA and TKA) have demonstrated excellent mid- and long-term outcomes and have been compared in clinical series for decades; however, to our knowledge, no study has sufficiently matched UKA and TKA cohorts on preoperative osteoarthritis severity. The purpose of this study was to evaluate patient-reported outcomes of radiographically and demographically matched UKA and TKA cohorts. Methods: One hundred and thirty-five … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 40 publications
(17 reference statements)
2
12
0
Order By: Relevance
“…This case also illustrates the nuanced approach necessary to diagnose discomfort after arthroplasty procedures. Although patients undergoing UKA demonstrate greater levels of postoperative satisfaction than patients undergoing TKA, 10% of patients are not satisfied with the function of the operative knee 10 . Patients undergoing UKA face a significantly higher rate of revision surgery than patients undergoing TKA, which may be partially attributed to real or perceived contribution of the native patellofemoral and contralateral compartment to a patient’s continued discomfort 11 .…”
Section: Discussionmentioning
confidence: 99%
“…This case also illustrates the nuanced approach necessary to diagnose discomfort after arthroplasty procedures. Although patients undergoing UKA demonstrate greater levels of postoperative satisfaction than patients undergoing TKA, 10% of patients are not satisfied with the function of the operative knee 10 . Patients undergoing UKA face a significantly higher rate of revision surgery than patients undergoing TKA, which may be partially attributed to real or perceived contribution of the native patellofemoral and contralateral compartment to a patient’s continued discomfort 11 .…”
Section: Discussionmentioning
confidence: 99%
“…A recent matched study of 135 TKAs and 135 UKAs reported both significantly improved pain and function, activity level, and satisfaction scores at 1-year follow-up for the UKA using the new Knee Society Score (KSS), the University of California Los Angeles (UCLA) activity-level score, and a Likert satisfaction scale respectively [ 31 ]. The Total Knee Questionnaire (TKQ) and the Forgotten Joint Score (FJS-12) have both demonstrated low ceiling effects in patient satisfaction measures and found UKA to be superior in this aspect [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“… 17 A recent radiographically matched cohort analysis gives further evidence towards improved PROMs in patients undergoing UKR, over those having TKR at one-year follow-up. 18 …”
Section: Ukrmentioning
confidence: 99%